40AR/39AR GEOCHRONOLOGY OF THE GRANITOIDS IN BEISHAN MOUNTAIN, NW CHINA - Jiang S.H.; Nie F.J. (My University, 2006)
The Beishan Mountain is located in north-western China and eastern-central part of the Central Asian Orogenic Belt. The granitoid intrusions are well developed and associated with copper, tungsten, gold and molybdenum mineralization in the region. In this paper, ten potassium-bearing minerals separates from granitoid samples are analyzed for the 40 Ar/39 Ar dating, of which six samples obtained reliable 40 Ar/39 Ar plateau age data, i. e. 352.3 ± 3.8Ma, 271.76 ± 0.88Ma, 286.2 ± 3.4Ma, 272.0 ± 4. 7Ma, 294.1 ± 2.9Ma and 255.2 ± 4.1Ma, respectively. They represent the emplacement age of the intrusions. Some useful age information can also be obtained from other four samples, even though they experienced strong late thermal disturbing. In addition, the Ar loss has been identified in six samples presented in this paper, mainly due to the late tectono-thermal events. Since the K-feldspar of the sample NSS01-13 lost much Ar, its reliable plateau age cannot be obtained. The Ar loss predominantly occurred during the time period of early Yanshanian, and partly of Indosinian. The 40 Ar/39 Ar age data in this paper, together with other published 40 Ar/39 Ar age data, indicate that multiple tectono-magmatic events occurred in Beishan region. Based on these age data, the magmatic activities in study area can be ascribed to five stages as follows since middle Hercynian movement: (1) 330~360MaMa, the middle Hercynian magmatic activity prior to the collision of Siberia, Kazakhstan and Tarim plates; (2) 270~310Ma, syn-collision granitoids associated with the collision of three plates; (3) 250~270Ma, post-collisional granitoids; (4) 210~250Ma, Indosinian tectono-magmatic activity; (5) 169~195Ma, early Yanshanian tectono-magmatic activity. Among these five stages, the granitoids occurring in the second stage, i. e. 270~310Ma, are predominant, with the largest outcrop area. Combined with other age data published by other authors, the most widespread granitoids of the Beishan region emplaced in late Hercynian, consistent with the collision time of the Siberia, Kazakhstan and Tarim plates. In contrast, the Indosinian and Yanshanian granitoids may be the products of the continental reactivation after the forming of the united continent. It can be concluded that the high precise age dating for granitoids in Beishan region is the key for building up the regional tectonic framework and re-constructing the tectono-magmatic evolutionary history. Meanwhile, these age data can also be used to direct the regional mineral exploration.
Keywords: 40AR/39AR GEOCHRONOLOGY; BEISHAN MOUNTAIN; GRANITOIDS